Hubungan peran perawat sebagai edukator dengan kepatuhan menjalani hemodialis pada pasien gagal ginjal kronik - Imas Yoyoh; Nuraini Rangkuti; Catur Suksesty (Health Sciences and Pharmacy Journal, 2020)
Chronic kidney failure is one of the uncontagious diseases which is increasing in the world and in Indonesia. A person who has last stadium chronic kidney failure requires hemodialysis therapy for a long time to maintain his life. Several previous studies have said that there were many factors can affect compliance, one of which is the role of nurses as educators. This study aims to determine whether there is a relationship between the role of nurses as educators and adherence to hemodialysis in patients with chronic kidney failure. The type of research used was descriptive correlation with cross-sectional design. The research instrument used was a questionnaire to assess the role of nurses as educators and adherence to hemodialysis. The sample was 24 respondents with total sampling technique. The test used was Fisher's exact test. The results of this study showed that 37.5% (9 people) of respondents had a bad nurse role, while 62.5% (15 people) of respondents got a good nurse role. Respondents who comply with hemodialysis were 62.5% (15 people), while respondents who did not comply were 37.5% (9 people). The results of the statistical correlation test obtained p value = 0.000 (p value 0.05). The conclusion is that there is a relationship between the role of nurses as educators and adherence to hemodialysis in patients with chronic kidney failure.